THE EFFECT OF THE TGT MODEL ASSISTED BY THE ‘PLAY WITH DYNO’ SNAKES AND LADDERS MEDIA ON FIRST GRADE STUDENT’S MATHEMATICS LEARNING OUTCOMES - Putra, Fahrizal Ananda; Setyawan, Agung (Widyagogik, 2025)
This study aims to determine the effect of the cooperative learning model of the Teams Games Tournament (TGT) type assisted by the snakes and ladders media "Play With Dyno" on the mathematics learning outcomes of grade I students at SDN Barurambat Kota 1 Pamekasan. The background of this study is the low student learning outcomes due to conventional learning methods that are less interesting and the lack of interactive media. The method used is quantitative with a quasi-experimental design of Nonequivalent Control Group Design. The sample consisted of two classes, namely class IA as the experimental group and class IB as the control group. The instrument used was a multiple-choice test. The results showed a significant increase in student learning outcomes after the TGT model assisted by the snakes and ladders media was applied. This approach has been proven to be able to increase student involvement, facilitate understanding of number concepts, and create a fun and meaningful learning atmosphere. The conclusion of this study is that the TGT model with the snakes and ladders media "Play With Dyno" is effective in improving the mathematics learning outcomes of grade I students and is worthy of being used as an alternative learning strategy in elementary schools.